(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2020)
Pharmaceutical and textile industries widely use inorganic and organic components which undergo different chemical and biochemical reactions with the ground water systems. The removal of organic wastes from effluents was carried out using a composite adsorbent. Four different samples were collected from the Gonoshasthaya Antibiotic Limted, Gonoshasthaya Pharmaceuticals Limited, Pakiza Dyeing and Printing Industries Limited and Bangladesh Dyeing and Finishing Industries Limited. Synthetic effluents of four types were prepared maintaining a similar chemical average of the collected samples. All the samples contained a high concentration of TDS, TSS, TS, COD and BOD5. The composite adsorbent performed excellently for all the samples. The concentrations of the components contained in the waste water were analyzed by UV-Visible spectrophotometer and High Performance Liquid Chromatography (HPLC). After the treatment, the decreasing trend of the absorbance and total peak area indicated that the significant amount of effluent materials were removed. Bangladesh J. Sci. Ind. Res.55(3), 197-206, 2020